The Washback Effect of Reformed CET 6 Listening Comprehension Test - Jiamin, Xie; Jinyan, Lu; Tianyi, Ma (Asian Journal of Education and Training, 2021)
In China, the English Test Band 6 (CET6) is a national test that is used to assess the English proficiency of test-takers by the state with unified questions, unified fees, and unified organization of tests. It is held twice a year. This test has had a great impact on college students and college teachers. It was introduced in 1978. In 2016, the Ministry of Education reformed CET-6, especially in listening tests. The reformed listening test not only brings scenes and dialogues closer to daily life but also emphasizes the examination of students’ comprehensive English listening and speaking ability. From the perspective of learners, this paper draws on the theoretical models and empirical results of washback at home and abroad and studies the backwash of the reformed English CET-6 listening to learners’ listening learning through a questionnaire. To do the survey, the paper was surveyed by quantitative research methods with 60 samples in several public universities. After the collection and analysis of data, the authors have affirmed and determined this test has a significant washback effect on student learning.